The boundary behavior of homeomorphisms of the class Wloc1,1 on a plane by prime ends - Petkov, I.V. (Reports of the National Academy of Sciences of Ukraine, 2015)
The boundary behavior of the so-called regular mappings that are a natural generalization of quasiconformal mappings is studied. A number of effective conditions on the dilatation coefficient Kf for a homeomorphic extension of these mappings by prime ends in finitely connected bounded domains are found.